#### Answer

$(2x-y)(x^3-3)$

#### Work Step by Step

$2x^4-6x-x^3y+3y=2x^4-x^3y-6x+3y=x^3(2x-y)-3(2x-y)=(2x-y)(x^3-3)$

Chegg costs money, GradeSaver solutions are free!

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$(2x-y)(x^3-3)$

$2x^4-6x-x^3y+3y=2x^4-x^3y-6x+3y=x^3(2x-y)-3(2x-y)=(2x-y)(x^3-3)$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.